1976
DOI: 10.1152/ajplegacy.1976.231.6.1824
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of pellet egestion in great-horned owls (Bubo virginianus)

Abstract: To study the mechanism of oral pellet egestion in great-horned owls, bipolar electrodes and strain-gauge transducers were chronically implanted in the esophagus, muscular stomach, and duodenum of six owls. Recordings from conscious owls plus simultaneous radiographic observations revealed characteristic gastrointestinal motility patterns associated with egestion. Beginning at about 12 min before egestion, gastric contractions formed the final shape of the pellet and pushed it into the lower esophagus. The pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…The value is similar to that of spontaneous spike bursts (2.5 to 4.5 cpm) recorded from the thick gizzard muscle of roosters with implanted electrodes in the fed state (Clench and Mathias, 1996). These workers reported that each spike burst was associated with a slow wave complex, although previous workers had failed to demonstrate spontaneous slow wave activity in the gizzard of the chicken (Roche, 1974) or other avian species (Duke et al, , 1975(Duke et al, , 1976. The frequency is also close to that reported in fistulated ambulant turkeys (3.3 cpm) with implanted cannulas or electrodes and with implanted strain gauges (3.1 cpm) (Chaplin et al, 1992), but higher than that of spike bursts (0.7 to 1.9 cpm) recorded in chickens with implanted gizzard electrodes (Roche and Ruckebusch, 1978).…”
Section: Physiological Findingssupporting
confidence: 76%
“…The value is similar to that of spontaneous spike bursts (2.5 to 4.5 cpm) recorded from the thick gizzard muscle of roosters with implanted electrodes in the fed state (Clench and Mathias, 1996). These workers reported that each spike burst was associated with a slow wave complex, although previous workers had failed to demonstrate spontaneous slow wave activity in the gizzard of the chicken (Roche, 1974) or other avian species (Duke et al, , 1975(Duke et al, , 1976. The frequency is also close to that reported in fistulated ambulant turkeys (3.3 cpm) with implanted cannulas or electrodes and with implanted strain gauges (3.1 cpm) (Chaplin et al, 1992), but higher than that of spike bursts (0.7 to 1.9 cpm) recorded in chickens with implanted gizzard electrodes (Roche and Ruckebusch, 1978).…”
Section: Physiological Findingssupporting
confidence: 76%
“…12 min (Duke et al . ; Duke ; Denbow ). The pellet is formed by intense contractions of the ventriculus, which also move the pellet to the base of the oesophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Pellet formation in extant crocodilians is irregular (vs regular in birds) and the mechanism is very different from the specialized process in birds (Duke et al . ; Fisher ; Andrews et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Larger items are torn into manageable pieces before being eaten. The undigested parts of prey are compressed in the stomach and egested orally as a pellet (Duke et al, 1976;Sturkie, 1986).…”
Section: Pellet Analysismentioning
confidence: 99%